The Effect Of Intervention In The Form Of Short Message Service On Revisit Compliance Rate In Patients With Chronic Disease In Internal Disease Policy Of Binjai Hospital In 2022 - Mutia Maywinsih Jauhari; Chrismis Novalinda Ginting; Ali Napiah Nasution; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2022)
In today's growing medical environment, the efficiency of health services and patient satisfaction are often considered as important indicators of the quality of health services. However, the absence of patients according to the specified schedule is a common problem. Short Message Service (SMS) as a reminder and motivation is able to influence changes in patient behavior. The formulation of the problem in this study is how the effect of providing intervention in the form of SMS on the rate of follow-up visits in chronic patients in the internal medicine clinic of Binjai Latersia Hospital. The research design used was Quasi-Experimental with One-Group Pre-Post Test Design. The population in this study were all patients with chronic diseases in outpatient installations who underwent control at the internal medicine clinic of the hospital as many as 42 people for 3 months, with a total sample of 126 people. The results of the study show 5. There is an effect of providing intervention in the form of Short Message Service on increasing the number of repeat visits in doing a treatment.